2008
DOI: 10.1007/s10800-008-9739-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment and microstructure on the corrosion of magnesium alloy Mg-10Gd-3Y-0.4Zr

Abstract: The corrosion of Mg alloy Mg-10Gd-3Y-0.4Zr, in the as-cast (F), solution treated (T4) and aged (T6) conditions, was investigated in 5% NaCl solution by immersion tests and potentiodynamic polarization measurements. The as-cast (F) condition had the highest corrosion rate due to micro-galvanic corrosion of the a-Mg matrix by the eutectic. Solution treatment led to the lowest corrosion rate, attributed to the absence of any second phase and a relatively compact protective surface film. Ageing at 250°C increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 31 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…Moreover, in Mg-Gd-Y alloys Mg 5 (Gd+Y) intermetallics act as cathode and form galvanic corrosion couples with α-Mg matrix, accelerating corrosion [48,49]. Therefore, it can be deduced that the second phase particles in Mg-Dy-Gd-Zr also form galvanic corrosion cells with α-Mg matrix and this is consistent with the corrosion morphology (Fig.…”
Section: Corrosionsupporting
confidence: 78%
“…Moreover, in Mg-Gd-Y alloys Mg 5 (Gd+Y) intermetallics act as cathode and form galvanic corrosion couples with α-Mg matrix, accelerating corrosion [48,49]. Therefore, it can be deduced that the second phase particles in Mg-Dy-Gd-Zr also form galvanic corrosion cells with α-Mg matrix and this is consistent with the corrosion morphology (Fig.…”
Section: Corrosionsupporting
confidence: 78%
“…However, their poor corrosion resistance in comparison with other metals has greatly retarded further applications. Many intensive and extensive fundamental investigations and evaluations about the corrosion problem of magnesium alloys have been carried out during the past decade [1][2][3][4][5]. However, most of these investigations devoted their research work to the as-cast alloys, such as AZ91D and AM50.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that microstructure plays an important role in the corrosion performance of materials [5][6][7][8]. For instance, variation of the morphology, volume fraction and distribution of secondary phases can change the corrosion resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Liang [12] found that the presence of basecentred orthorhombic b 0 precipitates after ageing results in the decreased corrosion resistance of Mg-7Gd-3Y-0.4Zr. Ageing decreases the corrosion resistance with increasing ageing time to 193 h, due to the formation of precipitates (b 00 (DO 19 ), b 0 (cbco) and b 1 (fcc)) in Mg-10Gd-3Y-0.4Zr alloy [8]. Precipitates of different sizes may have different effects on the corrosion resistance of the alloy system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation